Application of Thermal Kinetic Models in Liquid Foods and Beverages with Reference to Ascorbic Acid, Anthocyanin and Furan – a Review - Dhakal, Santosh; Heldman, Dennis R (Journal of Food Science and Technology Nepal, 2019)
Food processors aim to preserve as much as desirable quality attributes without compromising food safety. The major challenge associated with the conventional heating method is to protect adequately desirable quality attributes like color, flavor, texture, nutrients and bioactive compounds to address the demands of modern health conscious consumers. One approach is to use kinetic models and adopt the principle of optimization. The purpose of this review is to summarize the principles and functions of thermal processing followed by the application of reaction kinetic models to estimate the impact of thermal process on the food components, namely microbial population, ascorbic acid, anthocyanin and furan in liquid foods and beverages. In addition, it illustrates how the model parameters can be used to optimize the process through time-temperature tolerance (TTT) curve. Furthermore, it explains the significance of high temperature short time process for selected food components.